Hubungan Aktivitas Fisik dengan Kepuasan Hidup pada Lansia di Pusat Pelayanan Sosial Griya Lansia Ciparay - Sella Putri Herawadi; Lisna Anisa Fitriana; Septian Andriyani (Universitas Hamzanwadi, 2026)
Aging is a natural process accompanied by declines in physical, psychological, and social functions, which can affect life satisfaction among the elderly. Physical activity is known to support physical health, emotional well-being, and social interaction, potentially increasing life satisfaction in old age. This study aimed to examine the relationship between physical activity and life satisfaction among the elderly at the Griya Lansia Ciparay Social Service Center, West Java. This study used a quantitative correlational design with a cross-sectional approach. A total of 74 elderly were selected using purposive sampling based on predetermined inclusion and exclusion criteria. Physical activity was assessed using the Physical Activity Scale for the Elderly (PASE), while life satisfaction was measured using the Life Satisfaction Index-A (LSI-A). Data were collected through structured interviews to ensure that participants were able to understand the questions and recall their physical activity over the previous seven days. Data were analyzed using the Spearman correlation test. The results showed a significant positive relationship between physical activity and life satisfaction (p < 0.001; r = 0.441), indicating a moderate correlation. Elderly with higher levels of physical activity tended to report higher life satisfaction. This study suggests strengthening and diversifying physical activity programs to improve the well-being and life satisfaction of older adults in social care institutions.